Clinical outcomes of endocrine and other disorders induced by immune checkpoint inhibitors in Japanese patients - Yuichiro Iwamoto; Tomohiko Kimura; Kazunori Dan; Hideyuki Iwamoto; Junpei Sanada; Yoshiro Fushimi; Yukino Katakura; Masashi Shimoda; Shuhei Nakanishi; Tomoatsu Mune; Kohei Kaku; Hideaki Kaneto (Scientific Reports)
Abstract The purpose of this study was to analyze the efficacy of treatment and survival after administration of immune checkpoint inhibitor (ICI) in Japanese patients and had endocrine-related and/or other immune-related adverse events (irAEs), as well as irAEs in multiple organs. This is a single-center, retrospective, observational study of 571 Japanese patients treated with ICI at our hospital. We evaluated the occurrence of Grade 3 or higher irAEs and the life expectancy and treatment efficacy after ICI administration. Endocrine-related irAE (E-irAE), other irAE (O-irAE), endocrine-related and other irAE (EO-irAE), and multiple endocrine-related irAE (ME-irAE) were evaluated in groups. 80.8% of patients had an irAE, with the highest incidence of irAE with ipilimumab plus PD-1 inhibitor, followed by atezolizumab 59.0%, pembrolizumab 53.7%, avelumab 50.0%, and nivolumab 47.3%, Durvamumab 26.7% followed; Kaplan-Meier survival curves showed higher survival rates in patients with irAE compared to non-irAE, and higher survival rates in EO-irAE and ME-irAE compared to E-irAE and O-irAE (p < 0.001). The COX proportional hazard ratios for overall survival were E-irAE 0.611 (0.480–0.772), O-irAE 0.758 (0.597–0.957), EO-irAE 0.622 (0.466–0.819) and ME-irAE 0.463 when non-irAE was set at 1.000 (0.257–0.775). When grade 3 or higher irAEs appeared, regardless of their type, there was a trend toward higher survival and post-treatment remission rates after ICI administration. In addition to this, patients with irAEs in multiple endocrine tissues and patients with irAEs in both endocrine and other organs had a better response to treatment after ICI administration.